Az innovációs tevékenység mérési módjai és Magyarország innovációs teljesítménye nemzetközi összehasonlításban - Keresztes, Gábor; Székely, Csaba (Közép-Európai Közlemények, 2013)
In this study, we are going to compare the current innovation performance of Hungary with that of its competitors and give guidance on how to promote the flow of innovation in Hungary thereby enhancing the efficiency of the R&D&I sector. These processes might be basics to recover from the economic crisis and make development at the beginning of 21st century.